(3CSGSjGJ Yde GdEOGQIs - (3Ydj(B, (3YHGSs ((3YeGf(B:s (3OGQ GdeSjQI ddfTQ ddJhRjY(B,s, 2004)
(3GdeHGOF GdMOjKI dYde GdGOGQI, eOGQS GdacQ GdGOGQj GdMOjK, GdJNWjW, YedjI GJNGP GdbQGQGJ hGfhGYgG hCSGdjHgG, GdJfXje GdGOGQj aj efXeGJ GdGYeGd, GdJhLjg h GdGTQGa, GdQbGHI GdGOGQjI, GdMGdGJ GdGOGQjI (B.s
(3HHdjhZQGajG(B: (3U U(B. 231-232s
Keywords: (3EOGQI GdCYeGds; (3GdEOGQIs